Analytical Study of the Selected Urdu Books about Intra-Faith Unity in Pakistan - Farman Ullah; Muhammad Ikramullah (Journal of Islamic and Religious Studies, 2017)
Whenever any issue regarding the religious matters was put up in the presence of the Holy Prophet (SAW), he himself explained that logically. The companions of the Holy Prophet (SAW) also sought his consent in such matters. However, there were some differences among the Companions (Saḥabas) regarding some of diligently-conceived views. Later on, such differences were multiplied and caused sectarian issues. In consequence of diligently-conceived opinions and efforts to address the issues of the Holy Qu’rān and Sunnah, four distinct sects emerged. Moreover, such differences took a different form in the later years which further led to the heinous act of “Takfeer”. Currently, the mutual enmity is at a great premium especially in Pakistan. This article will introduce and analyze the selected books, trying to indicate strengths and weakness of the subject matter discussed in books, in addition to examine the methodologies used in.